2008
DOI: 10.1177/070674370805300402
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Approaches in the Treatment of Chronic Pain Patients—When Pills, Scalpels, and Needles are Not Enough

Abstract: Psychosocial and behavioural factors play a significant role in the experience, maintenance, and exacerbation of pain. Self-management is an important complement to biomedical approaches. Cognitive-behavioural therapy alone or within the context of an interdisciplinary pain rehabilitation program has the greatest empirical evidence for success. As none of the most commonly prescribed treatment regimens are sufficient to eliminate pain, a more realistic approach will likely combine pharmacological, physical, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
132
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(145 citation statements)
references
References 72 publications
6
132
0
7
Order By: Relevance
“…In fact, we have shown that Der p 5 can induce in rabbits IgG antibodies which strongly inhibit house dust mite-allergic patients’ IgE reactivity to Der p 5. Studies performed with recombinant allergens indicate that the induction of blocking IgG antibodies is an important mechanism in allergen-specific immunotherapy with recombinant allergens [32, 33]. It may therefore be expected that vaccination of house dust mite-allergic patients with rDer p 5 will also induce a robust Der p 5-specific and protective IgG response.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we have shown that Der p 5 can induce in rabbits IgG antibodies which strongly inhibit house dust mite-allergic patients’ IgE reactivity to Der p 5. Studies performed with recombinant allergens indicate that the induction of blocking IgG antibodies is an important mechanism in allergen-specific immunotherapy with recombinant allergens [32, 33]. It may therefore be expected that vaccination of house dust mite-allergic patients with rDer p 5 will also induce a robust Der p 5-specific and protective IgG response.…”
Section: Discussionmentioning
confidence: 99%
“…Areas that have been extensively explored are cardiovascular [120,161,162,163,164,165], gastrointestinal [166], pulmonary [167], neurological disorders [168], chronic pain [169,170], diabetes [171,172], HIV/AIDS [173,174], and cancer [175,176,177]. These interventions may improve lifestyle and self-management, coping, quality of life, distress (especially depression and anxiety), course of physical illness, treatment adherence, and reduction in utilization of medical services [157,158,159,160,161,162,163,164,165,166,167,168,169,170,171,172,173,174,175,176,177]. Dealing with the psychological distress of family caregivers is another important area of action [178].…”
Section: Integration Of Psychological Care Into Medical Treatmentmentioning
confidence: 99%
“…Diseases diagnosed in the prescription are shown in Fig. 3 [2][3][4] An analgesic (commonly known as painkiller) is a member of the diverse group of drugs used to relieve pain. Analgesic drugs act in a variety of ways on the peripheral and central nervous systems; they include paracetamol, NSAIDs such as diclofenac, narcotic drugs such as morphine, synthetic drugs having narcotic properties such as tramadol, and others.…”
Section: Resultsmentioning
confidence: 99%